Evaluation of seasonal patterns of hydraulic redistribution in a humid subtropical area, East China - Sun, Long; Yang, Lei; Chen, Liding; Yen, Haw; Zhao, Fangkai; Li, Shoujuan (Hydrological processes, 2020)
Antecedent soil moisture or soil moisture status has a great impact on hydrological processes. Hydraulic redistribution (HR), a widely observed phenomenon, is defined as water distributed (typically at night) from moist soil to drier soil via plant roots, which plays an important role in soil moisture replenishment. Knowledge on seasonal patterns of HR and on the relationship between HR and soil water use is not fully understood. We investigated temporal variations in HR and total daily water use (Δθ) at stands of camphor and peach by monitoring soil moisture content in a humid region in eastern China. HR at the three locations reached its maximum values in summer (0.68 mm d−1 to 1.15 mm d−1) at depths of 15 cm and 35 cm. Redistributed water replenished 41% of water depleted in the soil at a 5–45‐cm depth. Interestingly, normalized HR (i.e., HR/Δθ) showed a constant pattern during the growing season implying it is independent of seasonal climate alterations. This also indicated that HR had a stable effect on the replenishment of daily water use. Positive linear relationships between HR and Δθ were found at three measuring locations (camphor: R2 = .35, p < .01; peach1: R2 = .57, p < .01; peach2: R2 = .63, p < .01), suggesting a relatively stable inherent linkage between HR and Δθ. This study suggested that hydrological processes involving soil moisture status or antecedent soil moisture, needs to take the HR effect into account across timescales from intraday to seasonal. Positive linear relationship was found between hydraulic redistribution (HR) and total daily water use (Δθ) at the three monitoring locations. Normalized HR (i.e., HR/Δθ) showed a constant pattern during the growing season, implying it is independent of seasonal climate alterations. Hydrological processes involving soil moisture status or antecedent soil moisture needs take the HR effect into account across timescales from intra‐day to seasonal.